Empowering Galuh Surabayan Contemporary Woven Fabric Artisans in Community Development for Creative Tourism in Surabaya - Achmad Room Fitrianto; Ignatia Martha Hendrati; Nuruni Ika Kusuma Wardhani (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Covid-19 pandemic has huge impact. The negativity of this pandemic has affected all aspects, including the economy, especially in the MSMEs sector. One of the MSMEs affected by the Covid 19 Pandemic in Surabaya is Galuh Surabayan, an MSME that produced contemporary twisted batic (batik ikat). This paper examines the condition of the Galuh Surabayan, which have been affected by the Covid-19 pandemic and the assistance efforts taken to rise and develop tourism in Surabaya. Data collection techniques were carried out using Focus Group Discussion, observation, interviews, and documentation using the stages in the asset-based community development approach. There are five activities carried out, firstly, capacity building in media promotion and sales, Second, provide infrastructure facilities to improve the quality and quantity of Galuh Surabayan Woven Fabrics productivity. Third, marketing and sales assistance. Fourth, social media and marketplace training. Fifth, bookkeeping and financial training